2009
DOI: 10.1260/026361709788921588
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Sorption of Cd(II) and Pb(II) Ions from Aqueous Solution by Local Bentonite and Clinoptilolite

Abstract: Local clay (bentonite) and a zeolite (clinoptilolite) have been characterized and used for the removal of Pb(II) and Cd(II) ions from aqueous solutions using batch sorption experiments. Parameters such as the equilibrium time, the effect of pH and temperature were studied. The sorption capacities of the two sorbents were calculated by fitting the Langmuir adsorption model to the experimental data points. Metal ion sorption by zeolite

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This finding is in agreement with the order of binding constants for metallic ions with catechol derivatives [28]. This metallic uptake order was also observed by Moulay et al [20,21] and also when bentonite and clinoptilolite were employed as clay adsorbents [29].…”
Section: Metallic Adsorption-desorption Studysupporting
confidence: 90%
“…This finding is in agreement with the order of binding constants for metallic ions with catechol derivatives [28]. This metallic uptake order was also observed by Moulay et al [20,21] and also when bentonite and clinoptilolite were employed as clay adsorbents [29].…”
Section: Metallic Adsorption-desorption Studysupporting
confidence: 90%
“…One possible interpretation of this phenomenon is that Cd 2+ ions are well hydrated. To be adsorbed on soils, they have to lose the hydration shell which needs energy, so the removal of water molecules from Cd 2+ ions is an endothermic process in essence (Meng et al, 2008;Faghihian and Nejati-Yazdinejad, 2009). Several similar results were reported on Ni 2+ (Song et al, 2009) and Pb 2+ (Xu et al, 2008;Sheng et al, 2009) adsorption.…”
Section: Adsorption Characteristics Of Carbendazim and CDmentioning
confidence: 70%
“…Faghihian and Nejati-Yazdinejad [26] have studied the sorption of Cd(II) and Pb(II) ions by clinoptilolite under different experimental conditions in order to ascertain their potential as sorbents for the removal of these metal ions from aqueous solutions. The authors found that the removal of Pb(II) ions was much greater than that of Cd(II) ions under identical experimental conditions.…”
Section: Introductionmentioning
confidence: 99%